Universe of the mind : a semiotic theory of culture / Yuri M. Lotman ; translated by Ann Shukman ; introduction by Umberto Eco. - Lotman, IU. M. (IUri Mikhailovich) (Tauris transformations, 2001)
This is Lotman's seminal text in cultural semiotics, laying out the theoretical structure on which all his work is built for a new generation of readers engaged with critical theory and cultural studies, philosophy and historiography